Enhancing Customer Loyalty through Social Media Marketing and Brand Experience - Reni Rupianti; Nur' Adilla; Mariza Kertaningtyas (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2026)
This study aims to analyze the influence of social media marketing on customer loyalty by considering the mediating role of brand experience among consumers of modern coffee beverages, specifically Generation Z in Malang City. This study employs a quantitative approach with an explanatory design. Data were collected through an online questionnaire distributed to respondents who had purchased modern coffee products and followed the relevant brand’s social media accounts. The sampling technique used purposive sampling with specific criteria, and data analysis was conducted using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The results indicate that social media marketing has a positive and significant effect on brand experience and customer loyalty. Furthermore, brand experience was also found to have a positive and significant effect on customer loyalty and acts as a mediating variable in the relationship between social media marketing and customer loyalty. These findings indicate that the success of social media marketing strategies depends not only on the intensity of promotions but also on a brand’s ability to create memorable experiences for consumers. Thus, this study concludes that the integration of social media marketing with a strong brand experience can effectively enhance customer loyalty in the modern coffee industry.